2018
DOI: 10.1210/en.2018-00040
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Lipid Accumulation and Distribution by Agouti-Related Protein in Male Mice

Abstract: Proper regulation of energy metabolism requires neurons in the central nervous system to respond dynamically to signals that reflect the body's energy reserve, and one such signal is leptin. Agouti-related protein (AgRP) is a hypothalamic neuropeptide that is markedly upregulated in leptin deficiency, a condition that is associated with severe obesity, diabetes, and hepatic steatosis. Because deleting AgRP in mice does not alter energy balance, we sought to determine whether AgRP plays an indispensable role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…AgRP inhibits sympathetic activity in the white adipose tissue to limit lipolysis (38). We have also shown that intracerebroventricular infusion of AgRP suppresses sympathetic activity in the liver (29). Moreover, AgRP neurons mediate the stimulatory effects of leptin on sympathetic activity in the adipose tissue and liver (2).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…AgRP inhibits sympathetic activity in the white adipose tissue to limit lipolysis (38). We have also shown that intracerebroventricular infusion of AgRP suppresses sympathetic activity in the liver (29). Moreover, AgRP neurons mediate the stimulatory effects of leptin on sympathetic activity in the adipose tissue and liver (2).…”
Section: Discussionmentioning
confidence: 87%
“…The brain regulates peripheral lipid metabolism by modulating the function of the autonomic nervous system innervating peripheral metabolic tissues. In particular, the AgRP neuropeptide inhibits sympathetic nervous system (SNS) activity in both the white adipose tissue and liver (29,38). To this end, we sought to determine if intact SNS function is required for the development of hepatic steatosis induced by bingelike alcohol consumption.…”
Section: Chemical Sympathectomy Attenuates the Extent Of Hepatic Steatosis Induced By Bingelike Alcohol Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism for this occurrence is that loss of SORCS3 expressed in agouti-related peptide (AGRP) neurons leads to unchecked production of circulating AGRP ( Henry et al, 2015 ). ARGP is well described to cause enhanced food intake, decreased locomotor activity, decreased use of lipids as metabolic fuel, and overall increased adiposity ( Maier et al, 2018 ; Beutler et al, 2020 ). One limitation of GTEx data is a very small sample size of hypothalamus data, our data show that reduced expression of SORCS3 in the pituitary gland is related to high levels of TC and an increased overall risk for PAD, potentially through increased circulating AGRP diverting energy metabolism away from lipid sources.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct delivery of radiation to the tumor of the patient has been applied, radiotherapy induced acute and long-term damages to the surrounding normal tissues are still a common complication [1,5,21]. Radiation-induced esophagitis is one of the most common inflammatory reactions to radiotherapy in thoracic tumor [20,24,29].…”
Section: Introductionmentioning
confidence: 99%